(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The current research aimed to investigate the effect of using interactive videos on enhancing academic achievement in the Python programming language among first-year intermediate female students in the Digital Skills course. To achieve the objective of the study, the researchers employed a quasi-experimental design based on a one-group pretest-posttest approach. The treatment tool consisted of a set of interactive videos designed by researchers to cover the targeted Python topics. The assessment tool was an achievement test, also developed by researchers, to measure the students’ performance in the specified Python topics. The research was applied to a sample of 21 first-year intermediate female students from Khayf Al-Rawajeh School in Al-Jumum Governorate, Makkah Region. The participants were selected using the purposive cluster sampling method. The results of the research revealed a statistically significant difference at the level of significance (α = 0.05) between the mean scores of first-year intermediate female students in the Python programming language achievement test between the pre-test and post-test, with the difference favoring the post-test. The results also indicated that the use of interactive videos had a highly positive and significant impact on improving the academic achievement of first-year intermediate female students in the targeted Python programming topics: data input, Python operators, and drawing with programming. The effect size was notably large, with a rank correlation coefficient of (r = 0.823), indicating a high level of effectiveness of interactive videos in enhancing students’ academic performance. In light of these findings, several recommendations were presented, the most important of which are: the necessity of adopting the strategy of using interactive videos in teaching programming topics within the Digital Skills course, due to their effective and tangible impact on enhancing students’ academic achievement. Additionally, efforts should be directed toward developing and producing high-quality interactive videos that cover the remaining topics of the Digital Skills course and other computer science curricula, and making them accessible to teachers and students.